1997
DOI: 10.1016/s0896-6273(00)80360-8
|View full text |Cite
|
Sign up to set email alerts
|

Proteolipid Protein Is Necessary in Peripheral as Well as Central Myelin

Abstract: Alternative products of the proteolipid protein gene (PLP), proteolipid protein (PLP) and DM20, are major components of compact myelin in the central nervous system, but quantitatively minor constituents of Schwann cells. A family with a null allele of PLP has a less severe CNS phenotype than those with other types of PLP mutations. Moreover, individuals with PLP null mutations have a demyelinating peripheral neuropathy, not seen with other PLP mutations of humans or animals. Direct analysis of normal peripher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
114
0
2

Year Published

1997
1997
2008
2008

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 145 publications
(130 citation statements)
references
References 68 publications
14
114
0
2
Order By: Relevance
“…The relative importance of each of these molecules has been further proven by studies with mice deficient in each of these molecules. Thus, as expected, lack of Po in humans and mice causes demyelination in the PNS (Giese et al, 1992;Su et al, 1993), while mutations of the Plp gene have been shown to cause Pelizaeus-Merzbacher disease, spastic paraplegia type 2 and demyelinating disorders in a range of animal species (Garbern et al, 1997;Griffiths et al, 1995;Shy et al, 2003). Both of these proteins are responsible for the compaction of the intraperiod line of myelin which corresponds to two extracellular layers of plasma membranes adhering in a zipper manner (Shapiro et al, 1996).…”
Section: The Myelin Questionmentioning
confidence: 62%
“…The relative importance of each of these molecules has been further proven by studies with mice deficient in each of these molecules. Thus, as expected, lack of Po in humans and mice causes demyelination in the PNS (Giese et al, 1992;Su et al, 1993), while mutations of the Plp gene have been shown to cause Pelizaeus-Merzbacher disease, spastic paraplegia type 2 and demyelinating disorders in a range of animal species (Garbern et al, 1997;Griffiths et al, 1995;Shy et al, 2003). Both of these proteins are responsible for the compaction of the intraperiod line of myelin which corresponds to two extracellular layers of plasma membranes adhering in a zipper manner (Shapiro et al, 1996).…”
Section: The Myelin Questionmentioning
confidence: 62%
“…To explore the molecular components of the remyelination program, we applied AGCA to the peripheral nerve crush and transection injury expression profiles. Because MPZ, PMP22, MBP, MAG, periaxin, proteolipid protein (PLP), and the DM20 variant of PLP have all been shown to be critical for myelination, these genes, which we designate myelin gene anchors (MGAs), were chosen as anchors to identify other genes involved in the myelination process (1,22,23).…”
Section: Resultsmentioning
confidence: 99%
“…23 A mild PMD3 phenotype has been also reported for the other two nonsense mutations described in the first coding bases ATGG (delG3, delG4). 24,25 The mutation at the end of exon 3A (ACA-AAA) has been classified as a form of SPG. 26 This PLP mutation outside exon 3B may be responsible for a T115K amino acid substitution in PLP/DM20 but may also disturb the splicing of exon 3 resulting in the absence of DM20.…”
Section: Discussionmentioning
confidence: 99%